The implementation of nursing process during patient care in Ethiopia: A systematic review and meta-analysis. Issue 5 (May 2021) - Bayih, Wubet Alebachew; Ayalew, Metadel Yibeltal; Belay, Demeke Mesfin; Alemu, Abebaw Yeshambel; Birihane, Binyam Minuye; Asnakew, Sintayehu; Endalamaw, Aklilu; Demis, Asmamaw; Kebede, Solomon Demis; Abate, Biruk Beletew; Baih, Shegaw Zeleke; Feleke, Dejen Getaneh; et al.
Abstract: Background: Nursing process (NP) is a standard method of ensuring individualized holistic care through systematic assessment, diagnosis, planning, intervention and evaluation of patients. Its standard implementation is mandatory to meet the health target of "ensuring universal quality health-care services" in the sustainable development goals (SDG) launched by World Health Organization (WHO) in 2015. Being a member state of WHO, Ethiopia endorsed the SDG agenda. Therefore, determining the recent pooled estimate and associated factors of NP implementation during patient care would be of greatest importance to improve the quality of nursing care in the country. Methods: Primary studies were systematically searched from PubMed, Scopus, Cochrane Library, Google Scholar, PsycINFO and CINAHL data bases using different search operators. Each selected primary study was critically appraised using the Joanna Briggs Institute (JBI) appraisal tool for prevalence studies. I 2 and Q statistics were used to investigate heterogeneity. Given the substantial heterogeneity between the studies, random effects meta-analysis model was used to estimate the pooled magnitude of NP implementation. Subgroup analyses were performed for evidence of heterogeneity. Egger's test was considered to declare publication bias objectively. The PRISMA guideline was followed to report the results. Results: A total of 17 primary studies with a sample of 2, 819 nurses were included in this meta-analysis. The pooled estimate of NP implementation in Ethiopia was 50.22% (95% CI: 43.39%, 57.06%) with severe statistical heterogeneity (I 2 = 93.0%, P < 0.001) between the studies. From regional subgroup analysis, NP was least implemented in Tigray region 35.92% (95% CI: 30.86%–40.99%, I 2 < 0.001%). Egger's test showed no statistical significance for the presence of publication bias (P = 0.23). Nurses' good knowledge of NP [(Adjusted Odds Ratio (AOR) = 13.16: 9.17–17.15], nurses' Bachelor of Science (BSC) and above level of education (AOR = 4.16; 2.32–5.99), working in a stressful environment (AOR = 0.10; -0.02–0.22), training access (AOR = 3.30; 1.79–4.82) and accessibility of facility required for NP (AOR = 6.05; 3.56–8.53) were significantly associated with NP implementation at 95 % CI. Conclusions: It was found that only half of the nurses in Ethiopia implemented NP during patient care. Fortunately, its associated factors were modifiable. Therefore, the existing national efforts of increasing nurses' knowledge of NP and their level of education, availing facilities required for NP implementation, training access and ensuring non stressful working environment should be reinforced to meet the quality nursing care demand in Ethiopia. Prospero ID: CRD42019138159. Abstract : Nursing process; Ethiopia; Systematic review; Patient care.